THE HYBRID WORK PARADOX: RECONCILING FLEXIBILITY WITH COHESION THROUGH STRATEGIC LEADERSHIP AND HR SYSTEM REDESIGN - Nurhalimah; Ramon Zamora; Oktavianti (RADJA PUBLIKA, 2026)
This study examines the hybrid work paradox, where increased flexibility for employees may conflict with organizational cohesion, collaboration, and culture. Adopting a mixed-methods approach, the research integrates quantitative organizational metrics with qualitative insights from employees, managers, and HR professionals to explore how hybrid work impacts performance and engagement. The findings reveal that while hybrid models enhance autonomy, satisfaction, and productivity, they also create challenges related to communication, trust, and team alignment. Strategic leadership is identified as a key enabler in addressing these challenges, with trust-based management, inclusive practices, and effective communication fostering stronger cohesion. Additionally, the redesign of HR systems—such as flexible performance management and digital collaboration tools—supports the institutionalization of hybrid practices. The study also highlights persistent challenges, including inequities between remote and on-site employees and resistance to change. It concludes that organizations can reconcile flexibility and cohesion by integrating leadership strategies with adaptive HR systems, ultimately creating sustainable and high-performing hybrid work environments.